The sinus venosus myocardium contributes to the atrioventricular canal: potential role during atrioventricular node development?. Issue 6 (6th March 2015) - Kelder, Tim P.; Vicente‐Steijn, Rebecca; Harryvan, Tom J.; Kosmidis, Georgios; Gittenberger‐de Groot, Adriana C.; Poelmann, Rob E.; Schalij, Martin J.; DeRuiter, Marco C.; Jongbloed, Monique R.M.
Abstract The presence of distinct electrophysiological pathways within the atrioventricular node (AVN) is a prerequisite for atrioventricular nodal reentrant tachycardia to occur. In this study, the different cell contributions that may account for the anatomical and functional heterogeneity of the AVN were investigated. To study the temporal development of the AVN, the expression pattern of ISL1, expressed in cardiac progenitor cells, was studied in sequential stages performing co‐staining with myocardial markers (TNNI2 and NKX2‐5) and HCN4 (cardiac conduction system marker). An ISL1+/TNNI2+/HCN4+ continuity between the myocardium of the sinus venosus and atrioventricular canal was identified in the region of the putative AVN, which showed a pacemaker‐like phenotype based on single cell patch‐clamp experiments. Furthermore, qPCR analysis showed that even during early development, different cell populations can be identified in the region of the putative AVN. Fate mapping was performed by in ovo vital dye microinjection. Embryos were harvested and analysed 24 and 48 hrs post‐injection. These experiments showed incorporation of sinus venosus myocardium in the posterior region of the atrioventricular canal. The myocardium of the sinus venosus contributes to the atrioventricular canal. It is postulated that the myocardium of the sinus venosus contributes to nodal extensions or transitional cells of the AVN since these cells are located in the posterior region of the AVN. This finding may help to understand the origin of atrioventricular nodal reentrant tachycardia.